ENSO related fluctiations of rainfall and their consequences for some rodent populations in North Central Chile - Deane, Amy; Waylen, Peter (Tiempo y Espacio, 2015)
El Niño Southern Oscillation (ENSO) is evaluated for its effects on rainfall in semi-arid Chile. Daily precipitation records are used to identify biologically important rainfall events. Events are evaluated by crossing theory to derive estimates of the probability distributions of the number of events, dates of their annual first and last occurrence, and length of the critically important biologically wet season for three phases of ENSO. Biologically important rainfall events are most frequent during warm phases and least frequent during cold phases. Cold phases produce the earliest onset of the wet season, while neutral phases delay it. The importance of variation in rainfall and its association with rodent populations is discussed extensively.